Evaluating self‐efficacy for managing chronic disease: psychometric properties of the six‐item Self‐Efficacy Scale in Germany. Issue 1 (23rd August 2011) - Freund, Tobias; Gensichen, Jochen; Goetz, Katja; Szecsenyi, Joachim; Mahler, Cornelia
Abstract Objective Self‐efficacy – the confidence to carry out certain behaviour in order to achieve a specific goal – has increasingly been recognized as an essential prerequisite of effective self‐management of chronic diseases. Therefore, valid and reliable measures are needed to evaluate self‐efficacy in both research and clinical practice. This study explored the psychometric properties of the German version of the Self‐Efficacy for Managing Chronic Disease 6‐Item Scale (SES6G). Methods We performed standardized translation and cultural adaptation of the SES6G into German. The SES6G was externally validated with the German General Self‐Efficacy Scale (SWE). Cronbach's alpha, descriptive statistics and principal component analysis were used to assess psychometric properties of the SES6G. We assessed the effect of the number of co‐occurring chronic diseases on SES6G scores using linear regression modelling by controlling for age, gender and education level. Results We analysed data of 244 primary care patients in Germany. The SES6G showed good convergent construct validity to the SWE (spearman rank correlation 0.578, P < 0.001) and high internal consistency (Cronbach's alpha 0.930). Principal component analysis underlined the one‐dimensional structure of the instrument. Adjusted for age and gender, increasing numbers of co‐occurring chronic diseases were associated with lower SES6G scores (standardized β‐value −0.27, P < 0.001). Education level showed no significant effect. Conclusions The SES6G is a reliable and valid instrument to assess patients' self‐efficacy for managing chronic diseases. It may enhance further research in German‐speaking countries and appears to be a valuable measure for clinical practice.